Religion and Social Stratification in Multicultural Urban Society: A Bourdieuian Perspective - Hidayatulloh, Taufik; Saumantri, Theguh (Potret Pemikiran, 2025)
Religious and ethnic diversity in multicultural urban contexts often produces complex social dynamics, particularly in the formation of social stratification. This study examines these dynamics in Gang Luna Tolerance Village in Bandung City by explicitly applying Pierre Bourdieu’s theoretical framework—habitus, forms of capital, and social fields to analyse how religion and ethnicity structure everyday interactions and status hierarchies. Using a descriptive qualitative approach, data were collected through in-depth interviews with community leaders, residents from diverse religious and ethnic backgrounds, and local policymakers, as well as participant observation and document analysis. The findings reveal that religious habitus and the distribution of social and cultural capital play a significant role in shaping stratification patterns, while the arena of intergroup interaction in Tolerance Village encourages the negotiation of status positions. Although hierarchical differences exist, practices of religious tolerance embedded in community habitus strengthen harmonious relations and facilitate social mobility by expanding access to social capital. This study contributes to the sociology of religion by demonstrating how Bourdieu’s concepts explain the interplay between diversity and stratification in urban multicultural settings and offers insights for social policy development aimed at fostering inclusive, tolerant, and socially mobile communities in Indonesia.